Reflecting on "Marketing communications in health and medicine: perspectives from Willis-Knighton Health System": understanding the big picture - James K. Elrod; John L. Fortenberry (BMC, 2020)
Abstract Background Willis-Knighton Health System's special supplement in BMC Health Services Research, "Marketing communications in health and medicine: perspectives from Willis-Knighton Health System," focuses on advertising, public relations, sales promotion, and related communicative avenues, associated theory, and more. Across the supplement's articles, insights from the institution's experiences are presented, addressing the components of the marketing communications mix, foundational elements of communication, the patronage process, and the necessity for integrating marketing communications. Discussion As an understanding of the big picture is crucial in marketing communications, especially given that many of its components must be effected simultaneously, this particular article takes the insights provided in the supplement and presents them in an operational framework, demonstrating the marketing communications process. This framework concisely summarizes the facets profiled in the associated articles, permitting readers to see how these pieces work in concert with one another in health and medical settings, providing a basic communications structure which healthcare establishments can use to advance their patient engagement initiatives. Conclusions Health and medical providers must ensure that they possess a detailed understanding of core marketing communications facets, but as they acquire associated knowledge, they also must direct attention toward understanding the interrelationships between and among these facets, permitting a global perspective of communicative operations. This particular article summarizes insights from Willis-Knighton Health System's special supplement in BMC Health Services Research, providing a pathway toward realizing big picture marketing communications perspectives.